Population genetic structure and morphological diversity of Cruzia tentaculata (Nematoda: Ascaridida), a parasite of marsupials (Didelphinae), along the Atlantic Forest on the eastern coast of South America. Issue 11 (13th September 2022) - Souza, Renata; Vilela, Roberto do Val; Gentile, Rosana; Lopes-Torres, Eduardo José; Cordeiro-Estrela, Pedro; Moratelli, Ricardo; da Costa-Neto, Sócrates Fraga; Cardoso, Thiago dos Santos; Varella, Karina; Maldonado Júnior, Arnaldo
Abstract: Abstract: Cruzia tentaculata is a helminth parasite of marsupials and has a wide geographic distribution from Mexico to Argentina. The aim of this study was to analyse the genetic population structure of this nematode along the Atlantic Forest biome. Cruzia tentaculata specimens were recovered from Didelphis aurita, Didelphis albiventris and Philander quica in 9 localities. Morphological and morphometric data were investigated for phenotypic diversity among localities and hosts using multivariate discriminant analysis of principal components. Phylogenetic relationships of C. tentaculata were determined using maximum likelihood and Bayesian inference. The population structure was analysed by fixation indices, molecular variance analysis, Tajima's D and Fu's F s neutrality tests, Mantel tests and Bayesian clustering analysis. A higher significant morphometric difference for males was observed between localities. In the haplogroup networks, 2 groups were recovered, separating locations from the north and from the south/southeast. The morphometric variation in C . tentaculata between different localities was compatible with this north and southeast/south pattern, suggesting adaptation to different ecological conditions. Population genetic analyses suggested a pattern of evolutionary processes driven by Pleistocene glacial refugia in the northeast and southeast of the Atlantic Forest based on the distribution of genetic diversity.